ARMS TRADE BETWEEN UNITED KINGDOM WITH SAUDI ARABIA IN YEMEN CONFLICT ASSOCIATED WITH ARMS TRADE TREATY 2014 AND INTERNATIONAL LAW - Vera Ridhani (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
Abstract In March 2015, the Saudi-led coalition of nine Arab countries commenced its military operations against the Houthi rebels and the forces loyal to President Saleh. This operation included bombing raids to civilians and civilian objects, a blockade in the Gulf of Aden, which is causing widespread humanitarian suffering in Yemen. During the Yemen conflict, the United Kingdom has issued 152 military licenses and export arms to Saudi Arabia with a value of £ 2,8 billion. The arms exported by the United Kingdom and use of weapons by Saudi Arabia has resulted in serious violation of International Humanitarian Law. Furthermore, the United Kingdom, as a state party to the Arms Trade Treaty 2014, has violated Article 6(3) and Article 7 of the Arms Trade Treaty for exporting the weapons without conducting mitigation risk and assessment. This article aims to analyze the violations of the Arms Trade Treaty caused by the serious violations of International Humanitarian Law, as well as the violations of United Kingdom’s national law and framework governing arms exports. This article also argues that according to the International Law Commission Article on Responsibility of States for Internationally Wrongful Acts, the United Kingdom is responsible for the arms export that has caused damage to Yemen and should carry out compensation as a form of state responsibility. Keywords: Arms Trade Treaty, Export, Transfer Abstrak Pada Maret 2015, koalisi pimpinan Arab Saudi dan kelompok koalisi melakukan operasi militer melawan pemberontak Houthi dan pasukan yang setia kepada Presiden Saleh. Operasi ini termasuk serangan pemboman terhadap warga sipil dan objek sipil, blokade di Teluk Aden, yang menyebabkan penderitaan kemanusiaan yang meluas di Yaman. Selama konflik Yaman, Inggris telah menerbitkan 152 lisensi militer dan mengekspor senjata ke Arab Saudi senilai £ 2,8 miliar. Senjata yang diekspor Inggris dan penggunaan senjata oleh Arab Saudi telah mengakibatkan pelanggaran serius Hukum Humaniter Internasional. Lebih lanjut, Inggris sebagai negara pihak Arms Trade Treaty 2014 telah melanggar Pasal 6(3) dan Pasal 7 Arms Trade Treaty karena mengekspor senjata tanpa melakukan mitigasi risiko dan penilaian. Artikel ini bertujuan untuk menganalisis pelanggaran Arms Trade Treaty yang disebabkan oleh pelanggaran serius Hukum Humaniter Internasional, serta pelanggaran hukum nasional Inggris dan kerangka kerja yang mengatur ekspor senjata. Artikel ini juga berpendapat bahwa menurut International Law Commission Article on Responsibility of States for Internationally Wrongful Acts, Inggris bertanggung jawab atas ekspor senjata yang telah menyebabkan kerusakan di Yaman dan harus melakukan kompensasi sebagai bentuk tanggung jawab negara. Kata Kunci: Ekspor, Perjanjian Perdagangan Senjata, Transfer